Making handwash with the addition of chitosan as an antimicroba in Almujahidah foundation North Sumatera - Sinaga, Muhammad Zulham Efendi; Sihombing, Yuan Alfinsyah; Lukman Hakim (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Washing hands is a process to remove dirt and germs that cause diseases found on the skin of the hands by using water and soap. Washing hands is done because hands are often germ-carrying agents and cause pathogens to move from one person to another, either by direct contact or indirect contact. Washing hands with soap is very useful to kill germs on the hands. Clean hands will prevent transmission of diseases such as diarrhea, cholera, dysentery, typhus, intestinal worms, skin diseases, acute respiratory infections (ARI), bird flu or Severe Acute Respiratory Syndrome (SARS). Community service activities carried out at Almujahidah Foundation, located at Jalan Bilal Gang Makmur Lingkungan I, Sari Rejo sub-district, Medan Polonia in the form of training in making Handwash with the addition of chitosan as an antimicrobial. This activity is carried out with several methods, namely an initial survey of partner problems, conducting socialization about the importance of having a clean lifestyle by always washing hands using soap, conducting training on handwashing and monitoring and evaluation. During the public service process and evaluation and monitoring it has been concluded that students at the Almujahidah Foundation school have been able to make handwashes independently and continuously with the assistance of supervision from the teachers